Enhancing Ethyl Oleate Purity and Energy Efficiency in the Biodiesel Production Process Through Distillation Design Modifications - Rizki, Miftahul; Gabriaty, Luna; Rosyda, Nada Fauzi; Kusuma, Taruna Hadi (Journal of Chemical Engineering Research Progress, 2025)
The growing demand for renewable energy sources has driven research into more efficient biodiesel production methods. This study focuses on enhancing the purity and energy efficiency of ethyl oleate in biodiesel production through the transesterification of triolein using ethanol and sodium hydroxide. Two process designs were compared: a base process and a modified process incorporating the removal of the initial mixer, adjustment of distillation flow rates, and addition of a second distillation column. The modified process resulted in a higher ethyl oleate purity of 99.03% compared to 89.98% in the base case. Furthermore, energy savings increased to 57.66% and carbon emissions were reduced by 57.65%, demonstrating improved environmental performance. These findings suggest that process redesign can significantly improve biodiesel production quality and sustainability. However, further research is needed to assess economic feasibility using tools such as the Aspen Process Economic Analyzer (APEA) for potential industrial-scale implementation. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).